Study guides

☆☆

Q: 6b squared plus 11b plus 3?

Write your answer...

Submit

Still have questions?

Related questions

It is an algebraic expression that can be simplified to: 11b-7

5b - 3 - 2b = 6b - 3 3b - 3 = 6b - 3 3b - 6b = 3 - 3 b = 0

It is -10b - 7.

b2+11b-42 = (b+14)(b-3) when factored

104

3 squared plus 2 squared is equal to 13.

285

27

73

It is: b = -3

(8a - 3)(2b - 1)

3(g + 6b + 3r)

6 squared plus 3 is equal to 39.

1 squared (1x1) +3=4

When the sum of a number plus 3 is squared, it is 11 more than the sum of the number plus 2 when squared.

6 squared is 36. 36 plus 3 is 39

That is 9 + 16 + 5 which is 30.

3

7^2 + 3^2 = 58

9 plus 16=25 3 squared is the same as 3 times three and 4 squared is the same as 4 times 4 3 times 3 + 4 times 4 9 plus 16 = 25

109 = 9 + 100

9x squared plus 16 = 0 factored is plus and minus 4/3 i.

4x2 + 1 + x2 + 3 = 5x2 + 4

3 + 43 = 46 7 squared = 49 46 + 49 = 95

15.